Maternidad/maternalidad y trabajo: "efectos" del rol dual sobre las madres que trabajan - Ragúz, María (1990)
An overview of sex role literature and recent research on working mother is presented. Attention focuses con correlational and causal findings concerning the "effects" mother's dual work has on herself. The article constitutes a continuation of a previous one on the "effects" of mother's work on her children and husband.